2020
DOI: 10.2147/prbm.s284103
|View full text |Cite
|
Sign up to set email alerts
|

<p>Moving More and Sitting Less as Healthy Lifestyle Behaviors are Protective Factors for Insomnia, Depression, and Anxiety Among Adolescents During the COVID-19 Pandemic</p>

Abstract: Purpose This study aimed to investigate associations of physical activity time (PAT) and sitting time (ST) independently and jointly with insomnia, depressive and anxiety symptoms among Chinese adolescents in the context of COVID-19. Methods A cross-sectional study including 965 adolescents (mean age = 15.26, SD = 0.46) was conducted in May 2020. PAT, ST and the symptoms of insomnia, depression and anxiety were assessed with the International Physical Activity Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
103
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 71 publications
7
103
2
2
Order By: Relevance
“…This is an unsurprising finding because sedentary time has been repeatedly associated with deteriorated well-being components (e.g., depression) in large-scale epidemiological studies across adolescents [ 7 , 8 ] and adult populations [ 3 ]. Moreover, adolescents living in COVID-19 lockdowns have demonstrated increased sedentariness and low well-being [ 14 , 15 , 16 , 17 , 18 , 19 ]; sitting time in particular has dramatically increased [ 36 ] and clearly related with deteriorated well-being components including sleeping patterns and depressive and anxiety symptoms [ 43 ]. Tackling sedentary time in Greek adolescents during the COVID-19 pandemic and involved lockdowns should thus be prioritized to decrease sitting time modalities such as the widespread screen time.…”
Section: Discussionmentioning
confidence: 99%
“…This is an unsurprising finding because sedentary time has been repeatedly associated with deteriorated well-being components (e.g., depression) in large-scale epidemiological studies across adolescents [ 7 , 8 ] and adult populations [ 3 ]. Moreover, adolescents living in COVID-19 lockdowns have demonstrated increased sedentariness and low well-being [ 14 , 15 , 16 , 17 , 18 , 19 ]; sitting time in particular has dramatically increased [ 36 ] and clearly related with deteriorated well-being components including sleeping patterns and depressive and anxiety symptoms [ 43 ]. Tackling sedentary time in Greek adolescents during the COVID-19 pandemic and involved lockdowns should thus be prioritized to decrease sitting time modalities such as the widespread screen time.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have consistently shown that the relationship between lifestyles and mental health is bidirectional in nature ( Firth et al., 2019 , 2020a ). During the COVID-19 pandemic, research has mostly focused on the role of lifestyle behaviors as either risk or protective factors for common mental health symptoms and disorders ( Bendau et al., 2021 ; Cellini et al., 2020 ; Fullana et al., 2020 ; Lu et al., 2020 ; Novotný et al., 2020 ; Pham et al., 2020 ; Santabárbara et al., 2020 ; Stanton et al., 2020 ). Growing evidence supports that diet ( Fullana et al., 2020 ; Pham et al., 2020 ), physical activity ( Lu et al., 2020 ), and other lifestyle behaviors ( Cellini et al., 2020 ; Santabárbara et al., 2020 ; Stanton et al., 2020 ) are significant predictors of anxiety and/or depression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early data indicates that COVID-19 related closures, cancellations, and restrictions are associated with decreased cardiovascular tness (Dayton et al, 2021) and increased rates of obesity (Rundle et al, 2020) in children and youth. Reduced time spent in physical activity and increased time on screens during the COVID-19 pandemic have also been associated with greater risk of anxiety and depressive symptoms (Alves et al, 2021), and insomnia in children and youth (Lu et al, 2020). With most children and youth engaging in too much sedentary behaviour and screen time, and too little physical activity and sleep during the pandemic, it is speculated that this global health crisis could lead to future health consequences for this young generation.…”
Section: Summary Of Ndingsmentioning
confidence: 99%